Access to oil reserves - Mabro, R; Aït Laoussine, N; Daly, M; Poyanne, P (Oxford Institute for Energy Studies, 2007)
Robert Mabro assesses different aspects of the issue; Resource Nationalism: Nordine Aït-Laoussine asks what’s new? Michael Daly argues that the oil companies’ move to the technological frontiers is a response to the access problem; Patrick Pouyanné considers new stakes for companies and government and the need for renewed trust.